146k views
0 votes
Pls show solution tysm

Pls show solution tysm-example-1
User Streak
by
4.6k points

1 Answer

4 votes

Given:

The equation of curve is:


y=(2e^x)/(1+e^x)

To find:

The equation of the tangent line to the given curve at (0,1).

Solution:

We know that the slope of the tangent line at (a,b) is


m=(dy)/(dx)_((a,b))

We have,


y=(2e^x)/(1+e^x)

Differentiate with respect to x.


(dy)/(dx)=((1+e^x)(2e^x)'-2e^x(1+e^x)')/((1+e^x)^2)


(dy)/(dx)=((1+e^x)(2e^x)-2e^x(e^x))/((1+e^x)^2)

Slope of the tangent is


(dy)/(dx)_((0,1))=((1+e^0)(2e^0)-2e^0(e^0))/((1+e^0)^2)


(dy)/(dx)_((0,1))=((1+1)(2(1))-2(1)(1))/((1+1)^2)


(dy)/(dx)_((0,1))=((2)(2)-2)/((2)^2)


(dy)/(dx)_((0,1))=(4-2)/(4)

on further simplification, we get


(dy)/(dx)_((0,1))=(2)/(4)


(dy)/(dx)_((0,1))=(1)/(2)

The slope of the tangent line is
m=(1)/(2) and it passes through the point (0,1). So, the equation of the tangent line is


y-y_1=m(x-x_1)


y-1=(1)/(2)(x-0)


y-1=(1)/(2)x


y=(1)/(2)x+1

Therefore, the equation of the tangent line is
y=(1)/(2)x+1.

User Brett H
by
5.4k points